INOVASI PERENCANAAN BIAYA PENDIDIKAN BERBASIS KINERJA - Siti Halimah; Harsono MS (Jurnal Manajemen Pendidikan, 2026)
This study develops an innovative performance-based education cost planning model that links spending efficiency, traceable unit costs, and the achievement of educational performance indicators. A library research design was applied through a systematic literature review and qualitative content analysis of studies on performance-based budgeting, performance information quality, standard costs, education fund accountability, and costing methods such as activity-based costing. The synthesis indicates recurring constraints in public-sector budgeting, including education: weak traceability between expenditures and outputs/outcomes, a growing number of performance indicators with low renewal rates, and predominantly input-based standard costs that may not reflect output-based needs. At the institutional level, budgeting difficulties intensify when one activity contributes to multiple indicators, complicating cost attribution to performance targets and potentially weakening efficiency assessment. This study proposes an innovation comprising a Cost–Performance Matrix and a Unit-Cost Performance Dashboard, integrating activity–output–outcome mapping, activity-based unit cost calculation, and standard-cost benchmarking to enhance budget decision quality.